A Multicenter, Prospective Trial to Assess the Safety and Performance of the Spinal Modulation Dorsal Root Ganglion Neurostimulator System in the Treatment of Chronic Pain. Issue 5 (13th May 2013) - Liem, Liong; Russo, Marc; Huygen, Frank J. P. M.; Van Buyten, Jean‐Pierre; Smet, Iris; Verrills, Paul; Cousins, Michael; Brooker, Charles; Levy, Robert; Deer, Timothy; Kramer, Jeffery
<x xml:space="preserve">Abstract</x> Objectives This multicenter prospective trial was conducted to evaluate the clinical performance of a new neurostimulation system designed to treat chronic pain through the electrical neuromodulation of the dorsal root ganglia (DRG) neurophysiologically associated with painful regions of the limbs and/or trunk. Materials and Methods Thirty‐two subjects were implanted with a novel neuromodulation device. Pain ratings during stimulation were followed up to six months and compared with baseline ratings. Subjects also completed two separate reversal periods in which stimulation was briefly stopped in order to establish the effects of the intervention. Results At all assessments, more than half of subjects reported pain relief of 50% or better. At six months postimplant, average overall pain ratings were 58% lower than baseline (p < 0.001), and the proportions of subjects experiencing 50% or more reduction in pain specific to back, leg, and foot regions were 57%, 70%, and 89%, respectively. When stimulation was discontinued for a short time, pain returned to baseline levels. Discrete coverage of hard‐to‐treat areas was obtained across a variety of anatomical pain distributions. Paresthesia intensity remained stable over time and there was no significant difference in the paresthesia intensity perceived during different body postures/positions (standing up vs. lying down). Conclusions Results of this clinical trial demonstrate that neurostimulation of the DRG is a viable neuromodulatory technique for the treatment of chronic pain. Additionally, the capture of discrete painful areas such as the feet combined with stable paresthesia intensities across body positions suggest that this stimulation modality may allow more selective targeting of painful areas and reduce unwanted side‐effects observed in traditional spinal cord stimulation (SCS).